2011
DOI: 10.2320/matertrans.mb201013
|View full text |Cite
|
Sign up to set email alerts
|

Interface Reactions between Conductive Ceramic Layers and Fe-Cr Steel Substrates in SOFC Operating Conditions

Abstract: To improve contact resistance and protect the cathode from chromium poisoning, perovskite (La,Sr)CrO 3 , (La,Sr)CoO 3 and spinel MnCo 2 O 4 coatings were applied onto the surfaces of Fe-25Cr (DIN 50049) steel by means of the screen-printing method. The oxidation process of the coated steels under cyclic-oxidation conditions showed high compactness of the protective layer, good adhesion to the metal substrate, as well as acceptable area specific resistance level for SOFC metallic interconnect materials, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…8). [21,36] The considerable reduction in the vaporization rate was the result of the presence of a continuous, thin Mn 1.5 Cr 1.5 O 4 spinel layer formed on the outer part of the chromia scale as indicated by morphological and chemical studies of the oxidized DIN 50049 steel [21].…”
Section: Methods Of Sample Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…8). [21,36] The considerable reduction in the vaporization rate was the result of the presence of a continuous, thin Mn 1.5 Cr 1.5 O 4 spinel layer formed on the outer part of the chromia scale as indicated by morphological and chemical studies of the oxidized DIN 50049 steel [21].…”
Section: Methods Of Sample Characterizationmentioning
confidence: 99%
“…673 K. Above this To evaluate the effectiveness of the applied coating, chromium vaporization rate tests of uncoated and coated AL453 ferritic steel were carried out in humid air, for p(H 2 O) 0 9.7×10 −2 atm, at a flow a rate of 2×10 −6 m 3 s −1 and a temperature of 1,073 K, for 55 h, and under non-equilibrium conditions (unsaturated zone) [25]. Prior to each experiment, all samples were pre-oxidized in air at 1,073 K for 48 h. Figure 8 presents the chromium transport rate from the surface of uncoated AL453 steel and the steel coated with the Mn 1.5 Co 1.5 O 4 compared against the results obtained in [21,25,36] with regard to the Cr vaporization rate of uncoated DIN 50049 steel and the exact same steel covered with three different types of material coatings-(La, Ca)CrO 3 , (La, Sr)CrO 3 , and (La, Sr)CoO 3 -and with the sintered Cr 2 O 3 sample for reference [21].…”
Section: Methods Of Sample Characterizationmentioning
confidence: 99%
“…For a demanding role such as an ITSOFC interconnect, the total interconnect ASR must remain below 0.1 Ωcm 2 for proper performance 31 . However, compared to insulating phases such as Cr 2 O 3 and MnCr 2 O 4 , some authors may consider the formation of SrCrO 4 somewhat favorable to the overall performance of the interconnect 42,58 because the service life may be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Perovskite cobaltite coatings interact with the stainless steel and a new phase is formed, SrCrO 4 29,41 . However, the electrical behavior of these phases needs further investigation given that some authors 42 showed a beneficial effect whereas others 43 showed that this phase is non-conductive and that SrCrO 4 formation leads to lower conductivity.…”
Section: Introductionmentioning
confidence: 99%